2015
DOI: 10.1155/2015/382086
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Verapamil and Diltiazem in the Treatment of No Reflow Phenomenon: A Meta-Analysis of Randomized Controlled Trials

Abstract: Currently, there is still a lack of an optimal treatment for no reflow phenomenon (NRP). We analyzed the efficacy and safety of using nondihydropyridine calcium channel antagonists (NDHP, verapamil/diltiazem) in patients suffering from NRP. Eight RCTs with 494 participants were eligible for analysis. The pooling analysis showed that intracoronary verapamil/diltiazem injection significantly decreased the occurrence of the coronary NRP (RR: 0.3, 95% CI: 0.16–0.57; P = 0.0002) and reduced corrected thrombolysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
0
38
0
1
Order By: Relevance
“…Studies have reported a reduced risk of death associated with early treatment with nitroglycerin [ 19 , 20 ]. Verapamil and diltiazem, as vasodilators, can restore coronary artery flow and myocardial perfusion efficiently [ 21 , 22 ]. Beta-blocker therapy has been recommended in the course of MI for patients who are not at high risk for complications.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported a reduced risk of death associated with early treatment with nitroglycerin [ 19 , 20 ]. Verapamil and diltiazem, as vasodilators, can restore coronary artery flow and myocardial perfusion efficiently [ 21 , 22 ]. Beta-blocker therapy has been recommended in the course of MI for patients who are not at high risk for complications.…”
Section: Methodsmentioning
confidence: 99%
“…Both drugs were found to be efficient in addressing no reflow. However, we found no publication on “local NTG” for an application addressing coronary spasm …”
Section: Discussionmentioning
confidence: 95%
“…Еще одним вариантом кардиопротекции является ишемическое коронарное посткондиционирование, суть которого заключается в проведении серии циклических раздуваний баллона в просвете КА непосредственно после имплантации стента и восстановления [28] • Минимально инвазивная стратегия у избранных пациентов (П М) [32,33] • Ишемическое посткондиционирование (П М К) [34,35] • Механическая тромбэктомия (П М) [2] • Эксенатид, лираглутид (П) [36] • Оксид азота (П) [37] • Блокаторы кальциевых каналов (П М) [38] • Предсердный натрийуретический пептид (П) [36] • Гипотермия (П) [28] • Аденозин (П М) [39] • Прерывистая окклюзия коронарного синуса (П) [40] • Эксенатид, лираглутид (П) [36] • Предсердный натрийуретический пептид (П) [36] • Гипотермия (П) [28] • Аденозин (П М) [39] • Цилостазол (П) [42] Не рекомендовано…”
Section: анализ профилактических и лечебных тактикunclassified